Trends in economic research: an international perspective - Ana Rute Cardoso; Paulo Guimar\~aes; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2010)
Given the recent efforts in several countries to reorganize the research institutional setting to improve research productivity, our analysis addresses the following questions: To which extent has the recent awareness over international quality standards in economics around the world been reflected in research performance? How have individual countries fared? Do research quantity and quality indicators tell us the same story? We concentrate on trends taking place since the beginning of the 1990s and rely on a very comprehensive database of scientific journals, to provide a cross-country comparison of the evolution of research in economics. Our findings indicate that Europe is catching up with the US but, in terms of influential research, the US maintains a dominant position. The main continental European countries, Germany, France, Italy and Spain, experienced some of the largest growth rates in economic scientific output. Other European countries, namely the UK, Norway, the Netherlands, Denmark, and Sweden, have shown remarkable progress in per capita output. Collaborative research seems to be a key factor explaining the relative success of some European countries, in particular when it comes to publishing in top journals, attained predominantly through international collaborations.
Keywords: A10; I20; 330; Research performance; publications; rankings; Europe; North-America; US; Wirtschaftsforschung; Performance Measurement; Publikationsanalyse; Vergleich; Welt; USA; Europa